2006
DOI: 10.1002/bit.20827
|View full text |Cite
|
Sign up to set email alerts
|

Hydromechanical stress in shake flasks: Correlation for the maximum local energy dissipation rate

Abstract: Shake flasks are widely used in biotechnological process research. Bioprocesses for which hydromechanical stress may become the rate controlling parameter include those where oils are applied as carbon sources, biotransformation of compounds with low solubility in the aqueous phase, or processes employing animal, plant, or filamentous microorganisms. In this study, the maximum local energy dissipation rate as the measure for hydromechanical stress is characterized in shake flasks by measuring the maximum stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 57 publications
(93 reference statements)
5
56
0
Order By: Relevance
“…This is a further confirmation that the extreme and not the average values of e are relevant when considering processing suspension of containing dispersed particles. Similar conclusions were reported by other authors 83,84 when studying droplet breakup and found that the maximum stable droplet size scales with the maximum energy dissipation rate present in the system.…”
Section: Scaling Of Maximum Stable Aggregate Size With E Maxsupporting
confidence: 88%
“…This is a further confirmation that the extreme and not the average values of e are relevant when considering processing suspension of containing dispersed particles. Similar conclusions were reported by other authors 83,84 when studying droplet breakup and found that the maximum stable droplet size scales with the maximum energy dissipation rate present in the system.…”
Section: Scaling Of Maximum Stable Aggregate Size With E Maxsupporting
confidence: 88%
“…Our measurements, however, in agreement with the other few previous direct measurements (Zirbel et al 2000, Kaku et al 2006, show a much steeper relationship. Thus, the 2.8 relationship, which has been empirically tested (Büchs et al 2000, Peter et al 2006), seems to hold only for the range of conditions usual in shaking bioreactors, in which the volume of fluid is <20% of the nominal flask volume (e.g., Büchs et al 2000), and the frequency of oscillation is usually much higher. Under these conditions, the kinetic energy production rate is very high, typically above 5 × 10 3 cm 2 s -3 , and the bottom of the flask runs dry (Büchs et al 2000).…”
Section: Fig 4 Turbulent Kinetic Energy Dissipation Rate (ε) Plottementioning
confidence: 99%
“…In recent years, the knowledge about the conditions in shake flasks has increased. (Maier, 2002;Maier and Büchs, 2001;Maier et al, 2004) characterized the mass-transfer (Büchs et al, 2000a,b;Peter et al, 2004) characterized the power input, Peter et al (2006) the hydromechanical stress, and (Maier and Büchs, 2001;Peter et al, 2004) the fluid movement. Until lately shake flask experiments could be performed only in the batch mode of operation.…”
Section: Introductionmentioning
confidence: 98%